The remediation of oculomotor and attentional deficits of children with ADHD: identifying and training control mechanisms based on ocular data - Collins, Peter (2016)
This project set out to develop a cognitive training intervention for individuals with attention deficit hyperactivity disorder (ADHD). The thesis builds on research suggesting that reinforcement deficits in the ADHD population give rise to the underdevelopment of a number of cognitive abilities, in particular inhibitory control skills. Arguing that this skill is explicitly trainable and that training inhibitory gaze control is a means of training inhibitory control, this thesis set out to utilise eye-tracking technology to assess inhibitory gaze control performance in ADHD and to develop an engaging intervention in the form of a computer game capable of training the inhibitory gaze control system. Drawing on literature on inhibitory control in ADHD, the saccadic system, game development, and cognitive load theory a training intervention and battery of assessment tasks were developed iteratively across a number of pilot studies. The development process and resultant cognitive training interventions are described. The final proof-of-concept study was trialled for eight one-hour training sessions with an ADHD population (N = 8). Comparisons of pre- and post-training assessments produced strong effects for measures of gaze control, inhibitory control, timing, and attention. The results are interpreted and a number of limitations noted. The potential benefits of such interventions to aid clinicians to diagnose, to monitor, and to treat ADHD are considered. The relevance of cognitive interventions in contributing to research attempting to identify endophenotypes of ADHD is also discussed.